PERSEPSI MAHASISWA TENTANG PERANAN MATA KULIAH MICRO TEACHING TERHADAP KESIAPAN MENGAJAR PADA MAHASISWA PENDIDIKAN EKONOMI UNP - Nur Azizah; Elvi Rahmi (Jurnal Ecogen, 2019)
The purpose of this article is to analyze the effect of student perceptions about the role of micro teaching courses on student teaching readiness. This type of research is quantitative descriptive. The population of this research is the 2014 UNP FE Economics Education students who have completed the micro teaching course and the Education Field Experience Program course totaling 84 people. The sampling technique is saturated sampling (total sampling) so that the entire population is sampled. Research data are primary data collected by questionnaire. Instrument testing uses validity and reliability tests. Data were analyzed by descriptive and inductive analysis using normality test, heterocedasticity test, hypothesis testing using simple regression, t test and coefficient of determination with α = 0.05. The results showed that there was a significant and positive influence between students' perceptions of  the role of micro teaching courses on student teaching readiness, namely sig 0,000 <0,05. Keywords: Perception, Role, Micro Teaching, Teaching Readiness